2001
DOI: 10.1136/jcp.54.6.443
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological features and importance of p53, Rb, and mdm2 expression in phaeochromocytomas and paragangliomas

Abstract: Aims-Phaeochromocytomas and paragangliomas are uncommon. The aims of this study were to analyse the characteristics and the possible roles of p53, Rb, and mdm2 alterations in these tumours. Methods-The clinicopathological features of 65 patients (31 men, 34 women) with phaeochromocytomas or paragangliomas were analysed. The tumours were studied for the expression of p53, Rb, and mdm2 by immunohistochemical methods. Results-Thirty nine of the patients had phaeochromocytomas and 26 had paragangliomas. Bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 19 publications
1
22
1
Order By: Relevance
“…However, we observed a significant correlation between the presence, intensity, and staining proportion of cytoplasmic MDM2 protein expression and MDM2 gene amplification, implying that MDM2 gene amplification could have prognostic value in this specific subgroup of patients since cytoplasmic MDM2 proteins have been shown to play an important role in p53 inactivation [29]. There are conflicting data concerning whether cytoplasmic expression of MDM2 protein is true or false positive [30][31][32][33]. Given the correlation with gene amplification, we clearly demonstrated that cytoplasmic expression of MDM2 protein is true and relevant.…”
Section: Discussioncontrasting
confidence: 46%
“…However, we observed a significant correlation between the presence, intensity, and staining proportion of cytoplasmic MDM2 protein expression and MDM2 gene amplification, implying that MDM2 gene amplification could have prognostic value in this specific subgroup of patients since cytoplasmic MDM2 proteins have been shown to play an important role in p53 inactivation [29]. There are conflicting data concerning whether cytoplasmic expression of MDM2 protein is true or false positive [30][31][32][33]. Given the correlation with gene amplification, we clearly demonstrated that cytoplasmic expression of MDM2 protein is true and relevant.…”
Section: Discussioncontrasting
confidence: 46%
“…The rarity, fluctuating definition and long evolution of malignant PCCs have been important limiting factors to the determination of histopathological criteria of malignancy: Locally invasive and metastasizing tumors were often analyzed indistinctly [8,12,158]. The mean follow-up period of benign PCC in studies exceeded scarcely 8 years, whereas the mean reported delay before the occurrence of metastasis was 8 to 12 years [8,9,154,155,[159][160][161][162][163][164].…”
Section: Pathological Aspectsmentioning
confidence: 97%
“…The immunostaining for VEGF-C was graded according to the established scoring method as previously reported (24). Specimens were counted as negative immunoreactivity when there were <5% of tumor cells having a definite positive staining.…”
Section: Methodsmentioning
confidence: 99%